Orality workshop: an innovation proposal to improve oral expression of students - Campos Maylle, Yusev Teodulo (2019)
Objective. To determine the influence of implementing an Orality workshop for students of regular basic formation at Educational Institution N° 32023 of Vinchos, in Huanuco, 2018. Methods. Research approach was quantitative, with a quasi-experimental design. Population comprised 22 students of regular basic formation at Educational Institution N° 32023 of Vinchos. Huanuco. Prior their parents or guardians’ consent. A checklist was applied on the Orality workshop to improve students’ oral expression. This checklist was previously validated. Hypothesis was verified using Wilcoxon test, considering a p <= 0.05. Results. In the entrance test, results of oral expression were similar in both experimental and control groups. After the intervention, it was found that the average of the experimental group was 1.65, while the control group was 0.35. This showed that students in the experimental group achieved better oral expression scores than those in the control group. Student’s T test was used to verify if these values are significant, obtaining a p <= 0,000. It demonstrated that the intervention of experimental workshops develop capacities related to oral expression in students, in comparison to the group that did not receive the intervention. Conclusion. Implementing an Orality workshop influenced the development of oral expression of the sample under study. Therefore, research hypotheses were accepted.